2013
DOI: 10.1155/2013/947072
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tight Junctions in Upper Airway Epithelium

Abstract: The mucosal barrier of the upper respiratory tract including the nasal cavity, which is the first site of exposure to inhaled antigens, plays an important role in host defense in terms of innate immunity and is regulated in large part by tight junctions of epithelial cells. Tight junction molecules are expressed in both M cells and dendritic cells as well as epithelial cells of upper airway. Various antigens are sampled, transported, and released to lymphocytes through the cells in nasal mucosa while they main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 86 publications
(94 reference statements)
2
111
0
1
Order By: Relevance
“…Airway epithelial cells form intercellular tight junctions via multiprotein complexes. We found that Y-27632 treatment downregulated expression of four genes that are essential to forming these junctions (36). These included the occludin gene and claudin genes 1, 4, 7, and 8 ( Figure 6D, Table E5).…”
Section: Y-27632 Treatment Modulates Expression Of Genes Involved In mentioning
confidence: 88%
“…Airway epithelial cells form intercellular tight junctions via multiprotein complexes. We found that Y-27632 treatment downregulated expression of four genes that are essential to forming these junctions (36). These included the occludin gene and claudin genes 1, 4, 7, and 8 ( Figure 6D, Table E5).…”
Section: Y-27632 Treatment Modulates Expression Of Genes Involved In mentioning
confidence: 88%
“…Besides its role as a selective and highly regulated physical barrier through the establishment of the intercellular apical junctional complexes between neighbouring airway epithelial cells (AECs) [8][9][10][11], airway epithelium also acts as a critical orchestrator of the airway immune response through the secretion of a wide repertoire of molecules, including antimicrobial peptides and proteins (eg, lysozyme, defensins, and protease inhibitors), antioxidants (eg, superoxide dismutase and glutathione), chemokines, and cytokines, in response to environmental stimuli [2,[12][13][14].…”
Section: Airway Epithelium As a Key Player In Orchestrating The Allermentioning
confidence: 99%
“…The nasal epithelium is a highly regulated, impermeable barrier formed by tight junctions (Takano et al, 2005;Holgate, 2008;Kojima et al, 2013a). Tight junctions are the most apical components of intercellular junctional complexes and they have fence and barrier functions in normal epithelial and endothelial cells (Schneeberger & Lynch, 1992;Gumbiner, 1993;Cereijido et al, 1998).…”
Section: Introductionmentioning
confidence: 99%